"How much is too much?" The social construction of elite youth athlete exercise tolerances from the coaches` perspective - Schubring, A.; Bub, E.-M.; Thiel, A. (Journal of Sport and Social Issues, 2015)
Coaches are key actors in youth elite sport. As such, they are regularly confronted with professional problems that are both complex and highly consequential. Herein, we address one fundamental coaching problem: the definition of athletes` exercise tolerance levels. Drawing on the sociology of knowledge, we focus on coaches` conceptions of exercise tolerance and the sociocultural framing of their reflections. The qualitative analyses of 16 interviews with German youth elite sport coaches reveal that the coaches` understanding of exercise tolerances is changed by a variety of aspects (e.g., athletes` injury status, up-coming events, coaching philosophy). Furthermore, the coaches rely heavily on socioculturally shaped experiential knowledge. This results in subjective and flexible definitions of exercise tolerance, which are functional, but bear risks of inappropriate loading.